Implementation and control of a high gain DC-DC converter based on an active switched-inductor and passive switched-capacitor networks - Yong, Si Yin (2019)
The purpose of this project is to design and implement analog low-order current-mode controllers to regulate a high order DC-DC boost converter. These controllers are designed to satisfy the robustness and tracking capabilities criteria. Experimental results were provided to verify these criteria were met. The project was supposedly to be carried out in 2 stages, simulation followed by experiment. Computer simulation with the software PSIM has been of great importance contributing to this project. It was carried out to improve efficiency and give a gauge of what one should do. In addition, with simulation no risks are involved. However, in the report PSIM software results are not shown. Instead, only experimental results are shown.